2022
DOI: 10.3926/ic.1686
|View full text |Cite
|
Sign up to set email alerts
|

Strategic orientation to educational innovation: A systematic review and conceptual model

Abstract: Purpose: To carry out a systematic literature review on strategic orientation to educational innovation (SOEI), considering methodological and conceptual aspects.Design/methodology: Four macro-processes were implemented: identification (study location), description (information extraction), in-depth analysis (grouping and characterization patterns) and dissemination. The studies were identified through Scopus and Web of Science. The search expressions yielded 63 documents; afterwards, quality control was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…Additionally, a search strategy and protocol were developed to identify relevant databases and key terms for the search equation to find matches in article titles, abstracts, and content, along with the inclusion and exclusion criteria for selecting the study sample. Following similar guidelines to literature reviews focused on innovation management and current selection time frames (Betancur, Pardo del Val & Martínez-Pérez, 2022;Idris & Durmuşoğlu, 2021), the systematic literature review was conducted for academic products found between January 1, 2017, and September 9, 2021. Details of the strategies used are presented in Table 1.…”
Section: Stage 1: Planningmentioning
confidence: 99%
“…Additionally, a search strategy and protocol were developed to identify relevant databases and key terms for the search equation to find matches in article titles, abstracts, and content, along with the inclusion and exclusion criteria for selecting the study sample. Following similar guidelines to literature reviews focused on innovation management and current selection time frames (Betancur, Pardo del Val & Martínez-Pérez, 2022;Idris & Durmuşoğlu, 2021), the systematic literature review was conducted for academic products found between January 1, 2017, and September 9, 2021. Details of the strategies used are presented in Table 1.…”
Section: Stage 1: Planningmentioning
confidence: 99%